Sustained virological response rates with direct‐acting antivirals in black subjects with HCV genotype 1 infection: systematic analysis of clinical trials - Struble, Kimberly; Chan-Tack, Kirk; Qi, Karen; Valappil, Thamban; Connelly, Sarah; Mishra, Poonam; Price, Dionne; Murray, Jeffrey; Birnkrant, Debra (Journal of Virus Eradication, 2019)
Under representation of black subjects in trials of hepatitis C virus (HCV) direct-acting antivirals (DAAs) complicates assessment of differential outcomes for black individuals non-black individuals. HCV trials submitted to the Food and Drug Administration (2013-2017) to support approval or to expand an indication of 12-week interferon-free DAA regimens with or without ribavirin to treat HCV genotype 1 (GT1) infection were pooled to explore efficacy comparisons by ethnicity. Twenty-six trials were pooled and included 2869 individuals with HCV GT1 alone and 742 individuals with both HCV GT1 and HIV. Of the 2869 HCV GT1-mono-infected subjects, 408 (14.2%) were black. Sustained virological response assessed 12 weeks following cessation of treatment (SVR12) was 92%-100% in black individuals and 87.5%-100.0% in non-black individuals. In pooled analyses, SVR12 was numerically similar between black and non-black subjects (97.1% 97.3%). Baseline characteristics did not affect SVR12 for the two groups. Of the 742 subjects with both HCV GT1 and HIV, 243 (32.7%) were black: SVR12 was 89.5%-100% in black individuals and 94.4%-100% in non-black individuals. In pooled analyses for HCV GT1/HIV co-infection, black individuals had a 4% (95% confidence interval -7.7% to 0.3%) lower SVR12 than non-black individuals (93.4% 97.0%). This difference was driven by ION-4 in which study SVR12 was approximately 10% lower for black than for non-black individuals (89.5% 99.1%). Baseline characteristics did not affect SVR12 for the two groups. No notable SVR12 differences were seen in between black and non-black individuals with HCV GT1 alone. Although a numerical difference was observed between black and non-black individuals with both HCV GT1 and HIV, this finding was driven by results from a single trial and may be due to reasons other than ethnicity: 19 subgroup analyses showed baseline characteristics did not affect SVR12 for black and non-black individuals with both HCV GT1 and HIV.